Taurolidine in Pediatric Home Parenteral Nutrition Patients. Issue 2 (February 2017) - Hulshof, Emma Claire; Hanff, Lidwien Marieke; Olieman, Joanne; de Vette, Susanna; Driessen, Gert-Jan; Meeussen, Conny; Escher, Johanna Caroline
Abstract : To reduce the incidence of catheter-related bloodstream infections in home parenteral nutrition patients, the use of taurolidine was introduced in the Sophia Children's Hospital in 2011. This introduction led to a reduction in catheter-related bloodstream infections: 12.7/1000 catheter days before the use of taurolidine, compared with 4.3/1000 catheter days afterwards (n = 7) [relative risk = 0.36, 95% confidence interval: 0.20–0.65 ( P = 0.018)].